Determination of defects and damage modes in kenaf-reinforced epoxy composites under fatigue loading using thermal imaging and SEM techniques - Mat Jusoh, Suriani (2012)
In engineering design, concerns arose on the fatigue behaviours of composite materials.Much effort has been done to estimate the fatigue life by which destructive techniques were commonly used. Recently, non-destructive techniques (NDT) are increasingly being used on composite materials to detect defects. Parallel to the development, shifting interests from traditional monolithic materials to fiber reinforced polymer based materials have been demonstrated by researchers and engineers. Nevertheless, information on the use of NDT on natural fiber reinforced composite materials is still sparse. The present study was set out to detect defects and estimate fatigue life in natural fiber reinforced composite materials. In making the composite, kenaf bast was used as a reinforcement fiber with epoxy as the matrix. The NDT employed to serve the study purposes are Infrared (IR) thermal imaging and optical microscope. In parallel,destructive technique (DT) was also used in this study specifically in carrying out the fatigue tension-tension test and scanning electron microscope (SEM). By and large, the DT was used just to verify all the results by NDT. The advantages of using NDT via IR thermal imaging in kenaf reinforced epoxy composites to estimate the fatigue life are evidenced in the following results: IR has successfully detected five types of manufacturing defects in kenaf reinforced epoxy composites due to manufacturing process. The defects are voids, resin rich area, pockets of undispersed cross-linker, misaligned fiber and regions where resin has poorly wetted the fibers. Subsequently, IR thermal imaging has significantly determined fatigue damage in kenaf reinforced epoxy composites. In addition, fatigue damage modes has also been predicted and determined by the types of defects occurs due to manufacturing process. This proves that IR has successfully been a significant NDT in estimating fatigue life due to fatigue damage, proved experimentally and interpreted by the S-N curve. In terms of fatigue resistance, it is found that 60% fiber volume fraction kenaf reinforced epoxy composites specimen has the highest resistance at 119.71-53.20 MPa. Finally, based on damage accumulation, a model of fatigue life estimation, namely S-IR has been proposed.